YrDaily.Outfit / Nuradlina Bustami - Bustami, Nuradlina (2021)
First and foremost, the goal of this task is to allow students to explore, improve, and learn new skills learned in Principles of Entrepreneurship (ENT 530). Yr.DailyOutfit, or YDA BY ADLINA, is a business that provides the current style of outfit that matches the current situation. Furthermore, NurAdlina Binti Bustami is responsible as a seller and collaborates with several partners, one of which is the supplier who handles the stock of my product. Furthermore, my company provides a wide range of designs, colors, sizes, and prices for Shirts, Tops, Blouse, Skirts, Dress, and Pants. Aleya Petak, Mariya Blouse, Midi Skirt, and Alice Dress are some of the available outfits. Furthermore, our client is a customer with "buying power" who can contribute to my company's profit. This company's target market consists primarily of women, teenagers, and adults. We also want to appeal to customers who want to experiment and learn new ways to style their outfits. As a result, the importance of this target market is to ensure that our product and service share a common interest in meeting the needs of the customer. Furthermore, because of Covid-19, this business has only recently been established and operates online at No. 03, Jalan Cengal, Batu 9 Cheras, 43200 Selangor. The main activity of the business is to sell it through social media, specifically Facebook, which using delivery services such as J&T and Poslaju. The postage cost is determined by the customer's location. Moreover, we place a high priority on the quality and service that we provide, such as cooling fabric, lightweight fabric, cotton fabric, and linen fabric. Thus, this type of fabric is ideal for weather conditions in Malaysia, which has high humidity and a lot of rain due to its location on the equator. Last but not least, this task will allow you to investigate how we promote our business, as well as the skills and techniques we use in developing our business to achieve a satisfactory result. In Entrepreneurship, we must address four posting components. The first is Teaser Posting, which uses suspenseful, mysterious advertisements to pique an audience's interest and engagement in our services and goods (Ciotola, 2020). Following that, Soft Sell Posting is more focused on relationship building (Rodgers, n.d.). This method is used to demonstrate to prospective customers what services and products we have to offer. Furthermore, Hard Sell Posting is intended to persuade a customer to buy a product or service in the near future. Advertising or sales approach features are referred to as (Kenton, W. (2021). Last but not least, Frequency Posting is a posting that is made on a regular basis in order to create and engage with the customer (MayCreateDesign, 2019).